CYBERSECURITY IN WIRELESS BODY AREA NETWORK (WBAN): PROPOSING A PRIVACY AND SECURITY FRAMEWORK FOR WEARABLE HEALTHCARE DEVICES AGAINST CYBER-ATTACKS (Conferencea, 2022)
Having revolutionised the e-health technologies, the Wireless Body Area Networks (WBANs) has a great ability of collecting vital human body parameters through wearable sensors for further usage in various healthcare applications. WBANs have gained considerable attention of several health centres for making patient health monitoring processes easier and more affordable. These wearable devices are automatically measuring human blood pressure or insulin value and thus transmitting the data into hospitals. It is true that WBANs are contributing to improvement of health, however, the patient data before and after transmission out of the WBAN devices is subject to unauthorized access and manipulation. Thus, the security and privacy issues that come from WBANs usage in health monitoring is one of the major unresolved problems for the IoMT (Internet of Medical Things) researchers today and there is still a major gap for an integrated cyber protective framework to be specifically designed for all healthcare wearable devices of WBAN. This research focuses on fulfilling privacy and security requirements of WBAN users via proposing an integrated framework based on the results of primary and secondary research.